MICROPROCESSOR SYSTEM FOR TEMPERATURE INVESTIGATION OF AC MACHINES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The paper is about four channel microprocessor system for temperature measurement during static and running mode. It incorporates microcontroller type PIC18F452 and employs sensors which convert temperature into voltage. In addition it features optional connection to a PC for storing and processing amassed data. Based on this system a new method is proposed for analysing overheating and cooling of individual parts of asynchronous electric machines. A set of differential equations is derived which later on are processed by MATHCAD software. Obtained results can be presented in tabular or graphic form. The outcome of resolving this task is in the relative ease with which it is possible to establish overheat of various machine parts. Similarly, such approach could be applied with other types of electric machines.